Factors Affecting Generation-Z's Intention to Use GO-JEK - Melinda Melinda; Novia Vanessa Saputra (iBuss Management, 2019)
In the midst of Internet growth, many m-commerce businesses have merged into the market. Furthermore, Generation-Z consumers’ appearance has made businesses start to analyze on Gen-Z’s intention to use m-commerce. One of Indonesia’s m-commerce is GO-JEK who has become the pioneer in the m-commerce industry by successfully utilizing factors that can influence consumers’ intention to use. Based on the previous studies, there are nine factors that may possibly influence consumers’ intention to use GO-JEK. Those factors are perceived usefulness, perceived ease of use, perceived enjoyment, subjective norm, compatibility, innovativeness, variety of service, trust, and promotion.This research is using simple random sampling and has received responses from 136 eligible respondents. These data has run its validity, reliability, classical assumption tests, and multiple linear regression analysis. The result shows that from the nine independent variables, only perceived enjoyment, innovativeness, and promotion has influence over Generation-Z’s intention to use GO-JEK. Additionally, the promotion has been proven to be the most significant factor among others.           Keywords: Factors, Generation-Z, GO-JEK, Intention to Use